Basella alba, Grewia asiatica, Solanum nigrum and Ficus carica fruit extracts ameliorate the testicular histopathology induced by CCl4 exposure in albino mice: An experimental study - Syeda Nadia Ahmad; Khawaja Raees Ahmad; Usma Abdullah; Fiza Malik; Rabiyah Ali; Umara Amir-; Muhammad Ali Kanwal; Iram Inayat (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Carbon tetrachloride (CCl 4 ) is extensively used in various industries and induces oxidative stress in humans. Unfortunately, it is one of the neglected potent male reproductive toxicants. Objective: The present research reports the testicular histopathology of CCl 4 and ameliorations by four medicinal fruit pulp extracts (FPEs) in mice. Materials and Methods: Sixty male albino mice were divided into six groups (10/group) as per the following: 1. Vehicle control (Vc); 2. CCl 4 (C); 3-6. CCl 4 +Basella alba (CBa), CCl 4 +Solanum nigrum (CSn), CCl 4 +Ficus carica (CFc) and CCl 4 +Grewia asiatica (CGa). Except for the control group, CCl 4 (0.1 mL of 0.2 mL kg - 1 ) was given to the animals in corn oil. The four plant extracts (0.1 mL each) were respectively given to the relevant FPE group animals for the next five consecutive days, while the animals in the Vc and CCl 4 groups received water instead of FPE. Results: The CCl 4 exposure led to various histometric and histological alterations (loss of interstitial tissue and various dislodged tailless spermatids with enlarged heads) that were recovered in all except Solanum nigrum FPE mice post-treatment. The micrometric data of testicular sections also indicated significant decline in the number of spermatogonia, while the cross-sectional area of the sperm heads remained significantly higher in the CSn and C groups. Conclusion: Except for Solanum nigrum,the three FPEs, especially Ficus carica,showed rehabilitative properties against CCl 4 exposure-related modifications in testicular histopathologies.